Analisis Line Balancing pada Produksi Convert di PT. Medika Maesindo Global Temanggung - Widodo, Eko Muh; Ibahanif, Lely; Fatimah, Yun Arifatul (Borobudur Engineering Review, 2025)
PT Medika Maesindo Global is a manufacturer and exporter of personal protective equipment disposables for medical and industrial applications. Based on preliminary, it was found that unbalanced job distribution and resource efficiency. Thus it created idle time that reached 231,83 second in producing 1 coat velcro, and line efficiency value of 46% which created work in process by 4000 pce coat velcro per day. This research purpose to analyze line balancing on the convert production process using standard minute value method and ranked positional weight method. Result of the analysis using the two method shows that line efficiency reached 89% that increase by 43% from initial condition. Balance delay decreased to 43% from initial condition value of 54% to 11%. smoothness index decreased to 92 from initial condition value of 100 to 8. From the analysis it can be concluded that the proposed line more efficien than the existing line.